An Analysis of Authentic Assessment in English Textbook “Stop Bullying Now” Used for the Eleventh Grade Students of Senior High School - Ridwan, Ridwan; Wahyuningsih, Sri; Winarno, Winarno (Universitas PGRI Adi Buana Surabaya, 2021)
The objectives of the present research were to describe the characteristics of authentic assessment used in the English Textbook “Stop Bullying Now” and to find out the characteristics of the most dominant authentic assessment applied in the book “Stop Bullying Now” used for the eleventh grade students of senior high school. This research was a library research using a qualitative descriptive approach. The data which were obtained from document analysis were analyzed using concurrent activity flows from (Miles et al, 2014). The results of this research showed that the textbook had applied authentic assessments to all English skills: listening, speaking, reading, and writing. However, among the four skills, listening was the skill with the least activity. The textbook applied eight out of nine characteristics (realistic activity or context, cognitively complex, performance-based, formative assessment, collaborative, defense is required, multiple indicators or portfolio, and mastery expectation). The textbook did not apply the criteria known by students because it did not illustrate how teacher assessed students’ work. The most dominant criteria used in this textbook was realistic activity or context. This textbook also took a lot of materials related to the real-life of students.